Evaluation of Methodology for Serotyping Invasive and Nasopharyngeal Isolates of Haemophilus influenzae in the Ongoing Surveillance in Brazil - Bokermann, Sérgio (American Society for Microbiology, 2003)
To assess the magnitude of discrepant results obtained by routine Haemophilus influenzae serotyping, 258 isolates, collected by the epidemiological surveillance system in Brazil from individuals with invasive diseases or carriage, were evaluated by two slide agglutination (SlAg) methods: SlAg method 1, by which strains were initially screened with a serotype b-specific antiserum, and SlAg method 2, by which strains were tested against all serotype-specific antisera in parallel. Investigators comparing results of the two SlAg methods with those obtained by capsule type-specific PCR were blinded to the method used. The serotype prevalence rates found by the three methods were significantly different, involving discrepancies mainly between serotype b and noncapsulated (NC) isolates. For invasive isolates (n = 131), the overall agreement rate between SlAg method 1 or 2 and PCR was 68.0 or 88.3%, respectively, whereas for colonizing isolates (n = 127) the corresponding rate was 46.5 or 94.2%, respectively. SlAg method 2 improved the ascertainment of serotypes over that obtained with SlAg method 1, demonstrating good correlation with PCR. Use of the polyvalent antiserum as a screening reagent for SlAg for invasive and colonizing isolates showed poor discriminatory power, with a sensitivity of 65.8% and a specificity of 91.7%. We stress the importance of using a well-standardized SlAg methodology and suggest that reference laboratories should utilize PCR routinely to confirm SlAg results and to check all nonspecific SlAg reactions and apparent NC isolates by SlAg in order to provide reliable data on the prevalence of H. influenzae serotypes in the H. influenzae type b vaccine era.